2018
DOI: 10.1007/978-3-319-75608-0_9
|View full text |Cite
|
Sign up to set email alerts
|

Vehicle Classification Based on Convolutional Networks Applied to FMCW Radar Signals

Abstract: This paper investigates the processing of Frequency Modulated-Continuos Wave (FM-CW) radar signals for vehicle classification. In the last years deep learning has gained interest in several scientific fields and signal processing is not one exception. In this work we address the recognition of the vehicle category using a Convolutional Neural Network (CNN) applied to range Doppler signature. The developed system first transforms the 1-dimensional signal into a 3-dimensional signal that is subsequently used as … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 11 publications
0
19
0
Order By: Relevance
“…The use of DL methods for target classification in a 2D space, instead, have been studied in refs. [15], [124]- [131]. It is worth mentioning that, in the technical literature, the first results about the use of DL methods in automotive radar systems appeared after 2015, when it was found that DCNNs were able to simultaneously detect, localize and classify multiple targets by simply analysing 2D range-azimuth (or range-Doppler) maps.…”
Section: Autonomous Drivingmentioning
confidence: 99%
“…The use of DL methods for target classification in a 2D space, instead, have been studied in refs. [15], [124]- [131]. It is worth mentioning that, in the technical literature, the first results about the use of DL methods in automotive radar systems appeared after 2015, when it was found that DCNNs were able to simultaneously detect, localize and classify multiple targets by simply analysing 2D range-azimuth (or range-Doppler) maps.…”
Section: Autonomous Drivingmentioning
confidence: 99%
“…Besides, the lack of open-access datasets and benchmarks containing radar signals have contributed to the fewer research outputs over the years [ 18 ]. As a result, many researchers self-developed their own radar signal datasets to test their proposed algorithms for object detection and classification using different radar data representations as inputs to the neural networks [ 36 , 37 , 38 , 39 , 40 ]. However, as these datasets are inaccessible, comparisons and evaluations are not possible.…”
Section: Introductionmentioning
confidence: 99%
“…Research on exploiting DNNs for analyzing radar signals is still at an early stage. [6] considered the problem of classifying 6 different vehicles using the frequency-modulated continuous-wave (FMCW) radar signals, where Short Time Fourier Transformation (STFT) is firstly applied to the original radar signals to obtain spectrums as inputs to the DNN. In [7], the authors attempted to detect the presence of vehicles using DNNs, which can be formulated as a binary classification problem.…”
Section: Introductionmentioning
confidence: 99%